Determinação simultânea de sulfonilureias em plasma humano empregando cromatografia a líquido com coluna de meio de acesso restrito e coluna com partículas de núcleo fundido - Juliana Veloso Ferreira (2015)
Diabetes mellitus is one of the main causes of morbidity and mortality in the population and the sulfonylureas are widely used in the treatment. Currently, its determination in biological matrices is performed by conventional sample treatment techniques, which often leads to an increase of the total time of analysis and analytical errors. These limitations can be reduced by using columns with restricted access media (RAM), which allow the direct injection of biological fluids in chromatographic systems. Furthermore, the use of fused-core particles columns, allowing the use of high mobile phase (MP) flow rates, lead to a reduced total analysis time. Given the above, this study aimed to develop a bioanalytical method for the simultaneous determination of three drugs of the sulfonylurea class: glibenclamide, gliclazide and glimepiride in human plasma, using a two- dimensional high performance liquid chromatography (column switching automated) in backflush elution mode, with RAM column, as exclusion phase, coupled with a fused-core particle column. The average plasma protein exclusion percentages of the RAM column was 104.5%. The conditions of the method developed, for the first dimension, were: RAM-ADS column, MP consisting of ultrapure water pH 6.0, ate 1.0 mL min-1 flow rate and 3 minute turning valve time. In the second dimension was employed a guard column (C18) coupled with a fused-core particle column (C18), MP consisting of acetonitrile and 10 mM phosphate buffer pH 3.0 (54:46 v/v) with a 0.8 mL min-1. The elution time of the analytes was 1 minute, temperature was set at 35°C, injection volume set as 200 µL and wavelength detection was set as 230 nm. Flufenamic acid was used as internal standard. The total time of analysis, including the time related to de chromatographic step (8 minutes) and the time devoted to the extraction (3 minutes for protein exclusion and 1 minute for the analytes elution) was only 12 minutes.